2008
DOI: 10.1021/ac702403w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive DNA Detection Using Oligonucleotide−Silver Nanoparticle Conjugates

Abstract: Oligonucleotide-gold nanoparticle (OGN) conjugates are powerful tools for the detection of target DNA sequences due to the unique properties conferred upon the oligonucleotide by the nanoparticle. Practically all the research and applications of these conjugates have used gold nanoparticles to the exclusion of other noble metal nanoparticles. Here we report the synthesis of oligonucleotide-silver nanoparticle (OSN) conjugates and demonstrate their use in a sandwich assay format. The OSN conjugates have practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
184
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(190 citation statements)
references
References 28 publications
6
184
0
Order By: Relevance
“…The same strategy of ligand exchange has also been applied to Au rods (Dujardin et al 2001), silver nanoparticles (Thompson et al 2008), MPAstabilized CdSe/ZnS quantum dots (Mitchell et al 1999;Gill et al 2005) and Pt nanoparticles decorated with amino-modified DNA (Yang et al 2004).…”
Section: (I) Biotin Avidin and Derivativesmentioning
confidence: 99%
“…The same strategy of ligand exchange has also been applied to Au rods (Dujardin et al 2001), silver nanoparticles (Thompson et al 2008), MPAstabilized CdSe/ZnS quantum dots (Mitchell et al 1999;Gill et al 2005) and Pt nanoparticles decorated with amino-modified DNA (Yang et al 2004).…”
Section: (I) Biotin Avidin and Derivativesmentioning
confidence: 99%
“…This method of synthesis is clean, less costly, employs ambient conditions and less energy intensive . The diverse application of nanocrystalline silver ranges from catalysis (Jana et al, 1999) to photonics (Velikov et al, 2003), biosensing and diagnostics (Songping andShuyuan, 2005, Schultz et al, 2000), antimicrobial (Pal et al, 2007) DNA sequencing (Thompson et al, 2008). In one study, antimicrobial activity of silver nanoparticles was shown to promote wound healing (Ghosh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The most popular results based on such a nanoparticle assembly-based scheme have been comprehensively studied for the detection of DNA targets. For example, nanoparticle assemblies can be induced by combining two different types of DNAmodified silver nanoparticle (DNA-AgNP) probes with the target DNA sequence [36]. The two probe DNA sequences on the DNA-AgNPs are not complementary to the other, and therefore, the two types of DNA-AgNPs do not interact with each other and do stay dispersed in the absence of the target DNA.…”
Section: Lspr-based Detection Using the Assembly Formation Of Silver mentioning
confidence: 99%
“…The LSPR-based detection methods using assembly of spherical silver nanoparticles, or silver nanospheres (AgNSs), were first reported in 2008 by Graham et al [36]. Prior to their work, the AgNSs were demonstrated to be stably modified with probe DNA strands containing triple cyclic disulfide moieties by Mirkin et al [39,40].…”
Section: Silver Nanospheres (Agnss)mentioning
confidence: 99%